NILAI PENDIDIKAN KARAKTER DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Leni Julianti (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2014)
The lack of application of character education has a major influence on the progress of the quality of education. Education focuses more on cognitive aspects, even though character aspects are also very important to develop. The curriculum center, the Ministry of National Education has formulated character education materials that need to be developed, namely there are 18 character values. In the novel Laskar Pelangi is a literary work that contains a lot of character education values. The purposes of this research is to reveal about the value of character education and characteristics of Lintang in Laskar Pelangi Novel by Andrea Hirata. The approach used is descriptive qualitative with the type of research library research (library research). Data collection techniques using document analysis. The data analysis technique used is content analysis. The results of the study contained 18 values of character education in the novel Laskar Pelangi by Andrea Hirata, namely: religious, honest, tolerance, discipline, hard work, creative, independent, democracy, curiosity, national spirit, love for the homeland, respect for achievement, friendly or communicative, love peace, love to read, care for the environment, care about social, and responsibility very. There are 7 characteristics of latitude in the novel Laskar Pelangi by Andrea Hirata, namely: discipline, hard work, creative, independent, curiosity, love for the homeland, and love to read.